Development of test instruments to measure mathematical problem-solving skills in quadrilaterals and triangles - Norzilawati; Kartini; Hutapea, Nahor Murani (Program Studi Pendidikan Matematika Universitas Pasir Pengaraian, 2024)
The purpose of this research is to produce a test instrument to measure mathematical problem solving abilities on quadrilaterals and triangles in class VII SMP/MTs students. The test developed is in the form of a description that meets the criteria for logical and empirical validity, level of difficulty and good discriminating power. This research uses a development studies development model which consists of pleminary and formative evaluation stages. The formative evaluation stage consists of self-evaluation, expert review, one-to-one, small group and field test activities. The research instruments used were validation sheets, student response questionnaires and KPMM test questions. The research subjects were 33 students of class VIII.3 of SMPN 8 Pekanbaru. Research data was obtained by validating the test instrument with three validators and testing the test instrument with research subjects at the small group and field test stages. The results of the research show that the average score of test instrument validators for content, construction and language aspects is 87.82%, from the 20 questions developed, 20 questions were logically valid, and 17 questions were empirically valid with a reliability value of 0.90 in the category very high, while the level of difficulty obtained was 13 questions with a medium level of difficulty, 2 questions with an easy level of difficulty and 1 question with a difficult level of difficulty, and the distinguishing power was 9 questions in the good category, 6 questions in the sufficient category, and 2 questions in the poor category . Of the 20 questions developed, there were 17 questions that met the criteria for being logically and empirically valid and had a good level of difficulty and differentiating power.